2005
DOI: 10.1002/eat.20180
|View full text |Cite
|
Sign up to set email alerts
|

Parents' reports of the body shape and feeding habits of 36‐month‐old children: An investigation of gender differences

Abstract: Clinical and theoretical implications are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 29 publications
0
21
0
2
Order By: Relevance
“…Previous studies investigating gender differences have reported conflicting results. For example, some studies found no difference in parental misperception between boys and girls [17], [37], [38], while other studies found that parents were more likely to misperceive boys’ weight status compared to girls’ [39], [40]. Therefore, future studies that investigate this are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies investigating gender differences have reported conflicting results. For example, some studies found no difference in parental misperception between boys and girls [17], [37], [38], while other studies found that parents were more likely to misperceive boys’ weight status compared to girls’ [39], [40]. Therefore, future studies that investigate this are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…According to the previous studies, parents are not always worried about their offspring's weight or health despite the offspring's overweight status [15,17-19,27], especially if a child has a healthy appetite and eats healthy foods, such as fruits and vegetables [21]. Should parents be aware and worried of a child's overweight status, if the child is physically active and has healthy eating habits?…”
Section: Discussionmentioning
confidence: 99%
“…Although this research is beneficial, there is a body of literature suggesting that parents often underestimate their child's weight [8-14] thus indicating a need to explore environmental and social issues related to weight perception.…”
Section: Introductionmentioning
confidence: 99%
“…Parental perceptions of a child's weight may influence how a parent feeds their child [4,8]. One study reported that parents who accurately perceived their child's weight were more likely to believe their child was at risk for type 2 diabetes [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation